Reproductive efficiency through estrus resynchronization, timed artificial insemination and spermatozoa separation in beef cattle - Abd Malik, . (2012)
The objectives of this study were to improve resynchronization of oestrus, timing of artificial insemination and natural mating, verification of X- and Y-chromosomes after separation, and to analyze the motility, membrane integrity and acrosome integrity of bull spermatozoa. In the first experiment, a total 140 Brangus cows were synchronized with CIDR. Thirty to thirty five days after artificial insemination (AI), the cows were checked for pregnancy using ultrasound and those that remained open (non pregnant) were divided into two groups and resynchronized with either CIDR or two injections of PGF2α further at 11 days interval. All cows were observed visually for estrus response for a period of two hours at 12 h intervals, starting immediately after CIDR removalor after the second injection of PGF2α. Cows were in estrus when they were mounted at least 3 times during the period of observation. Following removal of CIDR and second injection of PGF2α, cows were inseminated at 60 and 70 h later, respectively. There were no significant differences (P>0.05) in estrus response and pregnancy rate between cows with initial synchronization and resynchronization used CIDR protocol. In Experiment 2, a total of 185 Brangus cows were randomly divided into two experiments. First, a total of 100 cows were randomly divided into three groups. Groups 1, 2 and 3 were artificially inseminated at 48-50 h (n=30), 53-55 h (n=29) and 58-60 h (n=41) after CIDR removal. The pregnancy rates were 26.6%, 24.1% and 36.6%., respectively. The pregnancy rate was higher in the G1 (36.6%) than the G1 (26.6%) and G2 (24.1%) groups, but not significantdifferent (P>0.05). Second, a total of 85 cows were divided into two groups. Group 1, consisted of 35 cows and further subdivided into seven sub-groups, consisting of 5 cows per group. Group 2 consisted of 50 cows which were artificially inseminated. At 58-60 h after CIDR removal, bulls were mixed in all sub-groups for one week (Group 1) and for Group 2, timed AI were conducted. The everage pregnancy rate in natural mating was 28.6%. The pregnancy rate in the timed AI group was 18.0%. However, the difference in the pregnancy rate in natural mating and timed AI groups were not statistically significant (P>0.05). In Experiment 3, verification of X- and Y-chromosome bearing spermatozoa separation by nested PCR and the motility and membrane integrity of the bull spermatozoa were evaluated. Semen samples were collected using an electro ejaculator from four Brangus bulls. Spermatozoa separation was conducted using three spermatozoa separation methods; (1) swimming speed using cervical mucus from estrus cows, (2) Percoll discontinuous gradient (45-90%), and (3) swim up using TALP medium. The nested PCR was used to verify the presence of X- and Y- chromosome. The motility and membrane integrity were also evaluated before and after spermatozoa separation. Primers were designed using amelogenin cDNA sequence with 329 bp and 266 bp X- and Y-bearing chromosome spermatozoa, respectively. Motility was analyzed using computer assist spermatozoa analysis (CASA) system, whereas the membrane integrity was analyzed using hypo-osmotic swelling test (HOST). These results were confirmed by the absence of a single band, either for X- or Y- chromosome. The double band indicating that the spermatozoa cannot be separated was observed, after separation. However, the percentage of X-chromosome spermatozoa in the swimming speed using cervical mucus from estrus cows media (58.33%), swim-up using TALP media (50%), while that in the Percoll gradient method was 44.33%. Statistically both percentage were significantly different (P<0.001) compared to the theoretical ratio (50:50). However, comparison of spermatozoa motility, membrane integrity, and concentration before and after separation showed significant differences (P<0.05) among them. In Experiment 4,the effect of extenders on the spermatozoa quality after cryopreservation were studied. Four extenders were used in this study namely cervical mucus collected from cows at estrus, Tris buffer, Sodium citrate and Tyrode’s albumin lactate and pyruvate (TALP).All of the extender aliquots were diluted to obtained sperm concentrations of 25 x 106 sperm/mL. Computer assisted semen analyses, hypo-osmotic swelling tests and fluorescence isothiocyanate-labelled peanut agglutinin (FITC-PNA) techniques were used to determine sperm motility, plasma membrane integrity and sperm acrosome integrity, respectively, in both fresh and frozen-thawed semen. The motility (74.9 ± 0.60%), membrane integrity (70.86 ± 0.81%) and acrosome integrity (67.31 ± 0.94%) of fresh ejaculates were higher than frozen-thawed semen. Sperm motility (47.93± 0.80%) was significantly higher (P<0.05) in cervical mucus extender than in the Tris buffer and TALP extenders. Furthermore, the levels of membrane (43.09 ± 0.83%) and acrosome integrity (51.67 ± 0.80%) of post-thawed spermatozoa in the TALP extender were significantly lower (P< 0.05) compared to the other three extenders. In conclusion, the cervical mucus extender resulted in sperm motility, membrane integrity and acrosome integrity comparable to that of the other tested extenders. However, acrosome integrity after thawing was higher than that observed with the TALP extender.